A method for theoretical calculation of Young’s modulus and modulus shear for metals and their alloys under normal conditions based on a new model of sound wave transmission in metal - Yurchenko Stepan A. (EPJ Web of Conferences)
The paper presents theoretical calculations of the values of Young’s modulus and shear modulus for single crystals of iron, chromium, and other metals and alloys based on a new model of sound transmission in metals. The theoretical values of Young’s modulus and shear modulus obtained for undeformed metals under normal conditions are slightly less than the values of Young’s modulus and shear modulus for these materials obtained experimentally, which is consistent with the condition of stress growth during elastic deformation.